2009
DOI: 10.1253/circj.cj-08-0668
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Plasma Granzyme B Levels After Acute Myocardial Infarction

Abstract: Background: Apoptosis is reported to play an important role in left ventricular (LV) remodeling after acute myocardial infarction (AMI). Granzyme B is a member of the serine esterase family, which has an important role in cellular apoptosis and extracellular matrix degradation. Methods and Results: Peripheral blood samples were obtained from 33 patients with a first-onset AMI treated by percutaneous coronary intervention (mean age: 61.4±8.7 years old) on days 1, 7 and 14 after onset. Plasma levels of tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…They also found that sustained levels of GrB was an independent factor for late-stage left ventricular remodeling. 234 The mechanisms by which GrB may contribute to plaque stability include ECM fragmentation, release of ECM-sequestered cytokines, and/or induction of macrophage or SMC apoptosis in the fibrous cap. To the latter point, Choy et al 135 showed, using a cell culture model, that GrB could induce SMC apoptosis in the absence of perforin through the disruption of SMC-ECM interactions and induction of anoikis.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…They also found that sustained levels of GrB was an independent factor for late-stage left ventricular remodeling. 234 The mechanisms by which GrB may contribute to plaque stability include ECM fragmentation, release of ECM-sequestered cytokines, and/or induction of macrophage or SMC apoptosis in the fibrous cap. To the latter point, Choy et al 135 showed, using a cell culture model, that GrB could induce SMC apoptosis in the absence of perforin through the disruption of SMC-ECM interactions and induction of anoikis.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Although traditionally viewed as a pro-apoptotic intracellular protease used by cytotoxic lymphocytes to induce target cell apoptosis, we and others have demonstrated the important role of extracellular GZMB activity in a number of chronic inflammatory diseases (reviewed in [15, 16]). GZMB accumulates in the ECM of inflamed tissues and is present in several bodily fluids in chronic diseases such atherosclerosis, chronic obstructive pulmonary disease (COPD) and RA [17, 18]. ECM proteolysis by GZMB leads to impaired tissue integrity in diseases.…”
mentioning
confidence: 99%
“…Elevated GrB plasma levels were detected in patients after acute myocardial infarction 38 and in patients with unstable carotid plaques, which correlated to increased cerebrovascular events. 39 However, a causative role for granzymes in atherosclerosis and plaque rupture requires further study as increased GrB in the plasma may, as discussed below, represent a potential extracellular role for this protease in disease.…”
Section: Granzyme-induced Apoptosis In Diseasementioning
confidence: 97%
“…68,69 Increased levels of circulating GrK are also associated with dengue fever. 68 In atherosclerosis, elevated GrB plasma levels are detected in patients with acute coronary syndromes 38 whereas GrB plasma levels are significantly higher in patients with unstable carotid plaques compared with those with stable lesions, and correspond to an increased incidence of cerebrovascular events. 39 These studies suggest that extracellular GrB activity contributes to ECM degradation and promotes plaque instability and rupture.…”
Section: Fibrillin-1mentioning
confidence: 99%